Assessment of Maternal and Neonatal Risk Factors for Tetralogy of Fallot among Children and Adolescents at Sulaimani Children’s Heart Hospital: A Cross-Sectional Study - H. Sadiq , Chia; M. Aziz , Pary; Husen Mohamad , Soran; Faeq Salih , Aso (Hammurabi Journal of Medical Sciences, 2025)
Background: Tetralogy of Fallot (TOF) is one of the most common congenital heart defects, and understanding the associated risk factors is crucial for developing preventive strategies and improving patient outcomes. Objectives: This study investigates the maternal and neonatal risk factors associated with Tetralogy of Fallot (TOF) among children and adolescents in Sulaimani City. The research was conducted at a specialized Children's Heart Hospital. Materials and Methods: A descriptive cross-sectional study was carried out, surveying 100 parents using a structured questionnaire. Results: The majority of TOF diagnoses (92%) occurred within the first year of life. Age distribution among the children showed that 26% were aged between 6-8 years, while 11% were under 3 years. Significant maternal factors associated with TOF included age during pregnancy, consanguineous marriage, and multiparity, which together accounted for a total variance of 20.842%. Maternal nutrition during pregnancy showed that 63% of mothers reported having a normal diet, 36% had poor nutrition, and 1% reported smoking during pregnancy. Additionally, 62% of the families had no history of heart disease, with the majority being of Kurdish nationality. Conclusion: Maternal factors such as mode of delivery, folic acid consumption three months before pregnancy, maternal habits, and diseases during pregnancy (including perinatal infections, anemia, and vitamin D deficiency) were significant contributors to the risk of TOF. The study recommends promoting a healthy diet during pregnancy and implementing educational programs to mitigate the identified risk factors.